A Comprehensive Review of DiagnoTech: Your Healthcare Companion - Mehreen Ibrahim Wagle; Mahesh Jadhav; Mitali Mahesh Dere; Mehvish Abdul Sattar Fansopkar; Vaishnavi Namdev Shegokar (International Journal of Mobile Computing Technology, 2024)
The review paper “A comprehensive review of DiagnoTech: Your Healthcare Companion” brings forth a transformative solution in the advancements of healthcare technology which aims to be an all-in-one Healthcare Companion. It explores the four key elements of DiagnoTech: Lab Tests, Body Mass Index (BMI) Calculation, Yoga and Diet Recommendations, and disease prediction. It brings to light each of these features’ functionalities, integration, and their collective impact on the healthcare industry. The lab test feature enables users to schedule appointments for medical tests at their preferred locations with the reports seamlessly provided in the DiagnoTech app as well as delivered via email. The BMI calculator allows users to monitor their health through body mass index calculations offering vital insights into overall wellness. DiagnoTech further provides personalized yoga and diet recommendations that are catered according to the needs. These suggestions not only support a better and healthier lifestyle but also the management and prevention of diseases. The paper delves into the predictive capabilities of DiagnoTech, explaining how the algorithms and data analysis help with early disease identification and prevention, thus lowering the burden of chronic illness. DiagnoTech provides a glimpse into the future of healthcare delivery where technology meets human well-being in the rapidly evolving healthcare ecosystem.
Keywords: BMI Calculation; DiagnoTech; Healthcare; Lab Tests; Yoga and Diet; disease prediction